SmartQ : design and development of a universal smart queuing system - Tan, Wua Fong (2017)
Queuing for services while waiting is inevitable. However, queuing causes waste of time and frustration. Mobile application technologies have advanced very quickly the past few years, it has been used to aid us in many daily tasks. Furthermore, the adoption rate of smart mobile devices which uses these applications has been increasing in an astonishing rate. Therefore, this project aims to make use of the mobile application technologies to develop queue management systems for smart mobile devices.